Pathophysiological pathways in patients with heart failure and atrial fibrillation . Issue 11 (23rd October 2021) - Santema, Bernadet T; Arita, Vicente Artola; Sama, Iziah E; Kloosterman, Mariëlle; van den Berg, Maarten P; Nienhuis, Hans L A; Van Gelder, Isabelle C; van der Meer, Peter; Zannad, Faiez; Metra, Marco; Ter Maaten, Jozine M; Cleland, John G; et al.
Abstract: Aims: Atrial fibrillation (AF) and heart failure (HF) are two growing epidemics that frequently co-exist. We aimed to gain insights into the underlying pathophysiological pathways in HF patients with AF by comparing circulating biomarkers using pathway overrepresentation analyses. Methods and results: From a panel of 92 biomarkers from different pathophysiological domains available in 1620 patients with HF, we first tested which biomarkers were dysregulated in patients with HF and AF ( n = 648) compared with patients in sinus rhythm ( n = 972). Secondly, pathway overrepresentation analyses were performed to identify biological pathways linked to higher plasma concentrations of biomarkers in patients who had HF and AF. Findings were validated in an independent HF cohort ( n = 1219, 38% with AF). Patient with AF and HF were older, less often women, and less often had a history of coronary artery disease compared with those in sinus rhythm. In the index cohort, 24 biomarkers were up-regulated in patients with AF and HF. In the validation cohort, eight biomarkers were up-regulated, which all overlapped with the 24 biomarkers found in the index cohort. The strongest up-regulated biomarkers in patients with AF were spondin-1 (fold change 1.18, P = 1.33 × 10 −12 ), insulin-like growth factor-binding protein-1 (fold change 1.32, P = 1.08 × 10 −8 ), and insulin-like growth factor-binding protein-7 (fold change 1.33, P = 1.35 × 10 −18 ). Pathway overrepresentation analyses revealed that the presence of AF was associated with activation amyloid-beta metabolic processes, amyloid-beta formation, and amyloid precursor protein catabolic processes with a remarkable consistency observed in the validation cohort. Conclusion: In two independent cohorts of patients with HF, the presence of AF was associated with activation of three pathways related to amyloid-beta. These hypothesis-generating results warrant confirmation in future studies. Graphical Abstract: